2007
DOI: 10.1080/00207450600582124
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery and Expression of GDNF Seen in Photochemically Induced Cerebral Infarction

Abstract: Glial cell line-derived neurotrophic factor (GDNF) is a potent neurotrophic factor involved in the survival and proliferation of neurons. However, there have been few reports examining the relationship between GDNF and functional recovery after cerebral infarction. The authors investigated the change in the expression of GDNF proteins during functional recovery in rats following photochemically induced cerebral infarctions. Functional recovery for the first 14 days after the infarction was evaluated using a be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…We previously evaluated recovery from hemiplegia and expression of brain-derived neurotrophic factor (BDNF) using a photochemically induced cerebral infarction model of the rat [2]. There are several advantages of using the photochemically induced cerebral infarction model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously evaluated recovery from hemiplegia and expression of brain-derived neurotrophic factor (BDNF) using a photochemically induced cerebral infarction model of the rat [2]. There are several advantages of using the photochemically induced cerebral infarction model.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to clinical rehabilitation, functional deficits resulting from stroke are long term. However, functional ability in the rat recovers to almost pre-infarct levels within 2 weeks after photochemical induction [1], [2]. A recent report that used a marmoset model of middle cerebral artery occlusion indicated that functional deficits were slow to recover [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to target the sensorimotor area of the cerebral cortex, green light with a 10 mm diameter was irradiated into the exposed skull 6 mm lateral to the midline and 4 mm posterior to bregma. Rose bengal was injected through the tail vein [15]. …”
Section: Methodsmentioning
confidence: 99%
“…Rose bengal was injected intravenously (20 mg/kg), and the sensorimotor area of the cerebral cortex was irradiated transcranially for 20 min. Irradiation was performed using green light (533-nm wavelength) and a fiber optic light guide of 10 mm diameter (MHF-G150LR, MSG10-1100S; Moritex, Tokyo) (Horinouchi et al 2007 Ohwatashi et al 2013 ). Animals were subsequently divided into 3 groups.…”
Section: Methodsmentioning
confidence: 99%